Interference with performance of a response selection task that has no working memory component: an rTMS comparison of the dorsolateral prefrontal and medial frontal cortex. - Hadland, K; Rushworth, M; Passingham, R; Jahanshahi, M; Rothwell, J (2001)
It has been suggested that the dorsolateral prefrontal cortex (DLPFC) is involved in free selection (FS), the process by which subjects themselves decide what action to perform. Evidence for this proposal has been provided by imaging studies showing activation of the DLPFC when subjects randomly generate responses. However, these response selection tasks have a hidden working memory element and it has been widely reported that the DLPFC is activated when subjects perform tasks which involve working memory. The primary aim of this experiment was to establish if the DLPFC is genuinely involved in response selection. We used repetitive transcranial magnetic stimulation (rTMS) to investigate whether temporary interference of the DLPFC could disrupt performance of a response selection task that had no working memory component. Subjects performed tasks in which they made bimanual sequences of eight nonrepeating finger movements. In the FS task, subjects chose their movements at random while a computer monitor displayed these moves. This visual feedback obviated the need for subjects to maintain their previous moves "on-line." No selection was required for the two control tasks as responses were cued by the visual display. The attentional demands of the control tasks varied. In the high load (HL) version, subjects had to maintain their attention throughout the sequence, but this requirement was absent in the low load (LL) task. rTMS over the DLPFC slowed response times on the FS task and at the end of the sequence on the HL task, but had no effect on the LL task. rTMS over the medial frontal cortex (MFC) slowed response times on the FS task but had no effect on the HL task. This suggests that a response selection task without a working memory load will depend on the DLPFC and the MFC. The difference appears to be that the DLPFC is important when selecting between competing responses or when concentrating if there is a high attentional demand, but that the MFC is only important during the response selection task.